Inhibition of adjuvant-induced TAM receptors potentiates cancer vaccine immunogenicity and therapeutic efficacy. (28th February 2021) - Llopiz, Diana; Ruiz, Marta; Silva, Leyre; Repáraz, David; Aparicio, Belén; Egea, Josune; Lasarte, Juan J.; Redin, Esther; Calvo, Alfonso; Angel, Matthew; Berzofsky, Jay A.; Stroncek, David; et al.
Abstract: Analyzing immunomodulatory elements operating during antitumor vaccination in prostate cancer patients and murine models we identified IL-10-producing DC as a subset with poorer immunogenicity and clinical efficacy. Inhibitory TAM receptors MER and AXL were upregulated on murine IL-10 + DC. Thus, we analyzed conditions inducing these molecules and the potential benefit of their blockade during vaccination. MER and AXL upregulation was more efficiently induced by a vaccine containing Imiquimod than by a poly(I:C)-containing vaccine. Interestingly, MER expression was found on monocyte-derived DC, and was dependent on IL-10. TAM blockade improved Imiquimod-induced DC activation in vitro and in vivo, resulting in increased vaccine-induced T-cell responses, which were further reinforced by concomitant IL-10 inhibition. In different tumor models, a triple therapy (including vaccination, TAM inhibition and IL-10 blockade) provided the strongest therapeutic effect, associated with enhanced T-cell immunity and enhanced CD8 + T cell tumor infiltration. Finally, MER levels in DC used for vaccination in cancer patients correlated with IL-10 expression, showing an inverse association with vaccine-induced clinical response. These results suggest that TAM receptors upregulated during vaccination may constitute an additional target in combinatorial therapeutic vaccination strategies. Highlights: Vaccination upregulates TAM receptor expression in monocyte derived IL-10+ DC. TAM blockade promotes DC activation, leading to enhanced vaccine immunogenicity. Vaccination plus TAM and IL-10 blockade has superior antitumor therapeutic effects. TAM levels in human cancer DC vaccines inversely correlate with clinical efficacy.